2020
DOI: 10.1002/glia.23926
|View full text |Cite
|
Sign up to set email alerts
|

Proton extrusion during oxidative burst in microglia exacerbates pathological acidosis following traumatic brain injury

Abstract: Acidosis is among the least studied secondary injury mechanisms associated with neurotrauma. Acute decreases in brain pH correlate with poor long‐term outcome in patients with traumatic brain injury (TBI), however, the temporal dynamics and underlying mechanisms are unclear. As key drivers of neuroinflammation, we hypothesized that microglia directly regulate acidosis after TBI, and thereby, worsen neurological outcomes. Using a controlled cortical impact model in adult male mice we demonstrate that intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 52 publications
1
65
0
Order By: Relevance
“…It is possible that the age-dependent protection seen in older KO mice is due to decreased transmigration and reactivity of neutrophils in the ischemic brain, rather than microglia-driven. Nevertheless, neuroprotection in young KO mice has been documented in models of traumatic CNS injury, hypoperfusion-induced white matter injury, and multiple sclerosis (Li et al, 2021;Ritzel et al, 2021). Moreover, our group (Ritzel et al, 2021) showed that protection persisted for weeks and months following TBI.…”
Section: Pathological Function Of Hv1 Channels Hv1 In Brain Aging and Age-related Pathologymentioning
confidence: 75%
See 4 more Smart Citations
“…It is possible that the age-dependent protection seen in older KO mice is due to decreased transmigration and reactivity of neutrophils in the ischemic brain, rather than microglia-driven. Nevertheless, neuroprotection in young KO mice has been documented in models of traumatic CNS injury, hypoperfusion-induced white matter injury, and multiple sclerosis (Li et al, 2021;Ritzel et al, 2021). Moreover, our group (Ritzel et al, 2021) showed that protection persisted for weeks and months following TBI.…”
Section: Pathological Function Of Hv1 Channels Hv1 In Brain Aging and Age-related Pathologymentioning
confidence: 75%
“…Nevertheless, neuroprotection in young KO mice has been documented in models of traumatic CNS injury, hypoperfusion-induced white matter injury, and multiple sclerosis (Li et al, 2021;Ritzel et al, 2021). Moreover, our group (Ritzel et al, 2021) showed that protection persisted for weeks and months following TBI. These findings indicate there could be important interactions between age, Hv1, and the onset, duration, and type of injury.…”
Section: Pathological Function Of Hv1 Channels Hv1 In Brain Aging and Age-related Pathologymentioning
confidence: 75%
See 3 more Smart Citations